BRIC agricultural policies through a WTO Lens - Brink, Lars; Orden, David; Datz, Giselle (International Food Policy Research Institute, 2017)
This chapter examines agricultural policies of the BRIC (Brazil, the Russian Federation, India, China) through the prism of the disciplines on domestic support under the Agreement on Agriculture (AoA) of the World Trade Organization (WTO).1 The effects of agricultural policies of the BRIC on production and trade have implications for their own domestic (and also global) food security as well as for world agricultural markets. As the BRIC have emerged as global economic powers, and their per capita incomes rise, questions intensify in a historical context about their governments’ future treatment of agriculture. We examine the obligations in the WTO of the BIC (Brazil and India, members since 1995, and China, which acceded in 2001) and how they have notified their agricultural support to demonstrate compliance with the rules and their commitments. The inclusion of the Russian Federation under the WTO disciplines in 2012 demonstrates the disciplines’ relevance even in the absence of a new agreement, and we discuss the disciplines on agricultural support established for the Russian Federation in its accession. We also assess the new rules that were negotiated in the Doha Round before it faltered at the end of 2008 as they would apply to the BRIC. While the prospect for adoption of new Doha disciplines has become remote, the negotiated provisions are informative about the future policy space the BRIC and other countries sought to maintain.